(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was carried out at an organized pig farm in Kalyani, West Bengal, to assess effectiveness of management practices like teat dipping and floor mopping on reduction of bacterial load and diarrhoeal incidence during pre-weaning period in piglets. Twenty lactating sows of Ghoongroo breed along with their newborn piglets (146 nos.) during pre-weaning period were studied. In group 1 (control) floor of each farrowing pen was washed with normal water. In group 2, additionally teats of each sow were treated with 10% povidone iodine dip. In group 3 floor of each farrowing pen was washed with normal water followed by mopping with 0.25% potassium permanganate. In group 4 both sow teat dipping and sty floor mopping with disinfectant was done. It was observed that the average bacterial load during the total pre-weaning period of 8 weeks was 48.4x103± 5.3 x103 cfu/cm2 in control group, whereas the average bacterial load was 34.0 x103±1.2X103 and 7.18 x102±0.10 x102 cfu/cm2 before and after teat dip application in group 2, and 32.5 x103±1.3 x103 cfu/cm2 and 6.98 x102±0.11 x102 cfu/cm2 in group 4, respectively, indicating positive impact of teat dipping as well as disinfectant floor mopping in reducing the bacterial loads of sow teats. Regular teat dipping and sty floor mopping can improve the body growth of piglets, by reducing the occurrence of piglet diarrhoea. Thus, the chances of economic losses in pig production unit can be reduced.